Merajut Kerukunan di Era Digital: Peran Gembala dalam Mengelola Pluralisme Agama di Society 4.0 - Terok, Djonny. N.; Suseno, Aji (Sekolah Tinggi Teologi Berita Hidup, 2024)
In the era of Society 4.0, advances in digital technology bring changes in human culture including the way humans interact, in the context of religious life. The growing religious pluralism demands a more adaptive role of pastors in knitting inter and interfaith harmony. Although digital advances facilitate interfaith dialogue, challenges remain in maintaining the values of spirituality and harmony in the midst of increasingly complex diversity. This research aims to build the role of pastors in managing religious pluralism in the digital era, and can build and strengthen interfaith harmony. Using a descriptive qualitative method with a literature study approach, it can be concluded that the role of pastors in facing the challenges of religious pluralism in the era of Society 4.0 is an important need in socialising. And pastors have an important role in guiding people to maintain harmony in religious diversity. Even the existence of digital technology can be used as a means to strengthen interfaith dialogue, but requires caution in approach and communication. So the role of pastors in the digital era is needed to create a deep understanding and reduce the potential for conflict between religious communities.Â Â Di era Society 4.0, kemajuan teknologi digital membawa perubahan dalam budaya manusia termasuk cara manusia berinteraksi, dalam konteks kehidupan beragama. Pluralisme agama yang semakin berkembang menuntut peran gembala yang lebih adaptif dalam merajut kerukunan inter dan antar umat beragama. Meskipun kemajuan digital memfasilitasi dialog lintas agama, tantangan tetap ada dalam menjaga nilai-nilai spiritualitas dan kerukunan di tengah keberagaman yang semakin kompleks. Penelitian ini bertujuan untuk membangun peran gembala dalam mengelola pluralisme agama di era digital, serta dapat membangun dan memperkuat kerukunan antar umat beragama. Menggunakan metode yang kualitatif deskriptif dengan pendekatan studi pustaka maka dapat disimpulkan bahwa peran gembala dalam menghadapi tantangan pluralisme agama di era Society 4.0 manjadi kebutuhan penting dalam bersosial. Dan gembala memiliki peran penting dalam membimbing umat untuk menjaga kerukunan dalam keberagaman agama. Bahkan adanya teknologi digital dapat digunakan sebagai sarana untuk memperkuat dialog antar agama, namun memerlukan kehati-hatian dalam pendekatan dan komunikasi.Â Sehingga peran gembala dalam era digital sangat dibutuhkan untuk menciptakan pemahaman yang mendalam dan mengurangi potensi konflik antar umat beragama.